Desenvolvimento do doce tipo canjica com amêndoa de baru - Machado Junior, Divino Ribeiro (2014)
The sweet hominy type is a traditional dessert typical of Brazilian cuisine and consumed in almost all regions of the country The use of kernels baru fragmented and low commercial value in their formulations, can contribute to adding value to fruit preservation of native species and sustainable regional development. This study aimed to develop and characterize physically and chemically, sweet caramelized hominy type and without caramel - traditional diet and lactose, almonds fragmented baru, which are considered by-products of the process of processing the fruit and low value commercial. Assessed the physical, chemical, microbiological and sensory, changes during the period of 4 months of storage, at room temperature (25°C (± 3°C)), and in the incidence of light. The data were analyzed: Proximal composition, calorific value, reducing sugar, non-reducing and total, pH, titratable acidity, water activity, color, texture, mold and yeast profile, coliforms at 45ºC, Salmonella, Bacillus cereus and Staphylococcus coagulase positive, as well as evaluation of the attributes of appearance, color, flavor and aroma, plus purchase intent. For hominy type caramelized sweet caramel and without - no lactose, became also the determination of isoflavones. The hominy type candy caramel caramelized and without - traditional, showed significant differences with regard to interaction of time and treatment for all physical and chemical analyzes. The products were stable, microbiologically for 4 months storage. For the sensory attributes of appearance, color, flavor and aroma reviews, candy obtained grades 8 and above, index higher intention to purchase 85%. For hominy type caramelized sweet caramel and without - diet, the interaction of time and treatment, significantly affect the physical and chemical quantification of all components surveyed, with the exception of moisture content. The diets candy remain microbiologically stable over the period of 4 months of storage. The grades for all sensory attributes evaluated (appearance, color , flavor and aroma ), were equal or greater than 7, and purchase intent index, greater than 70% for both products developed. Regarding sweet hominy type - lactose, interaction time and treatment, significantly influenced the physical and chemical quantification of all components evaluated. The isoflavones in the form of β - glycosides and aglycones in the two products was also developed, detected and these remained stable, microbiologically for 4 months storage. The two products developed, had purchase intent index above 85% and above 7 notes for the attributes appearance, color, flavor and aroma. The use of kernels baru fragmented and of low commercial value, was satisfactory from the point of view of technological and sensory, for all type hominy caramelized sweet caramel and without developed thus setting an alternative to the use and value to this by-product from the processing of the fruit.